A digital scheme to minimize the influence of transformer magnetizing inrush or CT saturation on line protection. (October 2018) - Liu, Penghui; Huang, Chun; Jiang, Yaqun; Yang, Yachao
Highlights: A digital scheme to eliminate distortion from line current signals is proposed. The distortion caused by transformer inrush or CT saturation is eliminated. After implementing elimination, the waveform of signal is reconstructed. The scheme minimizes adverse influences of transformer inrush and CT saturation. It contributes to the correct operation of line protection without interruption. Abstract: For transformer magnetizing inrush or current transformer (CT) saturation, conventional blocking techniques result in interruption or severe delayed operation of protective relays. Besides, the reliability of CT saturation blocking (or compensation/reconstruction) techniques may be also disturbed by transformer magnetizing inrush. For improvement, this paper proposes a digital waveform reconstruction scheme, instead of blocking techniques, to eliminate distorted portions caused by magnetizing inrush or CT saturation from current signals, which minimizes the adverse effects on line protection. Concretely, the proposed scheme implements the portion segmentation, distortion portion identification, distortion portion elimination, and waveform reconstruction, according to calculated real time amplitude and ratio of boundary gradient. Case test results indicate the correctness and effectiveness of the proposed scheme. It is able to repair the waveform of CT saturation current. Moreover, it opens a new door to eliminate magnetizing inrush component from current signals in power lines. The reconstructed current waveform without distortion is outputted in real time, which contributes to the uninterrupted correct operation of protective relays in power lines.